Critical information infrastructures security : 13th International Conference, CRITIS 2018, Kaunas, Lithuania, September 24-26, 2018, Revised selected papers /: 13th International Conference, CRITIS 2018, Kaunas, Lithuania, September 24-26, 2018, Revised selected papers. (2019) - Unknown
No abstract available